Engineered Waste Disposal Facilities - Rowe, R.; Fraser, Michael (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary The selection and design of an engineered waste disposal facility requires consideration of the potential for protection of ground-water quality, predictability of ground-water movement, and potential for disruption of ground-water users. In the design of a waste disposal facility, engineered systems are ofte nincorporated, and the service life of these systems must be considered when assessing their potential impact. The role of modelling in predicting the potential impacts due to the interaction between the hydrogeology and the proposed engineering is discussed, and the potential impact of different landfill designs on ground-water quality is examined.